(untitled) (Jurnal Pustaka, 2025)
This research aims to identify, examine, and analyze the use of affixes in Kunto Aji’s song Introduction to Purification of Thought. The research lasted for six months from December 2023 to May 2024. The method used in this research is descriptive qualitative method. The instrument in this research is the researcher himself. The object of this research is the album Introduction to Thought Purification. From the results of data analysis, 57 affixed words were found which include, prefixes as much as 38 data, suffixes as much as 8 data, confixes as much as 2 data, and combined affixes as much as 9 data. With this research, readers are expected to be able to explore the field of morphology, especially affixes in song albums.